A review of the Tillicera genus group with a revision of Plathanocera Schenkling (Coleoptera, Cleridae, Clerinae) - Gerstmeier, Roland; Stapel, Jessica (Zootaxa, 2016)
The Tillicera genus group is revised and defined to contain 40 species in the following six genera: Apopempsis Schenkling, 1903; Cardiostichus Quedenfeldt, 1885; Hemitrachys Gorham, 1876; Placocerus Klug, 1837; Plathanocera Schenkling, 1902 and Tillicera Spinola, 1941. The definition of the Tillicera genus group is mainly based on the presence of the dorsoventrally compressed and expanded antennae (from antennomere 3 onwards). The antennomeres are dilated at least from antennomeres 5 to 9 onwards, and are broader than long, always vested with dense long setae. A key to the constituent genera, color photographs, and distribution maps are provided. The genus Plathanocera is taxonomically revised, including a key to species and genital figures.